Clofazimine improves clinical outcomes in multidrug-resistant tuberculosis: a randomized controlled trial. (February 2019) - Duan, H.; Chen, X.; Li, Z.; Pang, Y.; Jing, W.; Liu, P.; Wu, T.; Cai, C.; Shi, J.; Qin, Z.; Yin, H.; Qiu, C.; et al.
Abstract: Objectives: We carried out a randomized multicentre study in China to investigate whether the clofazimine would improve the efficacy of the standardized regimen in patients with multidrug-resistant tuberculosis (MDR-TB). Methods: Patients with MDR-TB managed in 17 TB specialist hospitals in China between September 2009 and September 2011 were randomly assigned to the treatment groups at enrolment. In the intervention group, 100 mg clofazimine per day was added to the standardized regimen. The primary outcome was the proportion of patients with successful outcomes. Results: From the 156 patients that were screened, 74 were assigned to the control group and 66 to the clofazimine group. Of the 66 cases analysed for clinical outcome in the clofazimine group, 36 patients were cured, and seven completed treatment, yielding a favourable outcome rate of 65.1%. The proportion of patients with favourable outcomes receiving the control regimen was 47.3% (35/74), which was significantly lower than that in the clofazimine group (p 0.034, relative risk 0.661, 95% CI 0.243–0.949). Conclusions: The addition of clofazimine to the standard regimen improved the treatment of MDR-TB.